The efficacy of CT in the detection of right ventricular dysfunction in acute pulmonary embolism and comparison with cardiac biomarkers - In, Erdal; Sokucu, Sinem Nedime; Ozdemir, Cengiz; Aydin, Ayse Murat; Kuluozturk, Mutlu (European Respiratory Soc Journals Ltd, 2015)
[Abstract Not Available]
Keywords: Embolism; Biomarkers; Imaging